A study of 0-14-year-old children's access to health centers in rural areas using a buffer model (a case study of villages based in Kermanshah province, Iran) - Ali Almasi; Alireza Zangeneh; Shahram Saeidi; Razie Toghroli; Raziyeh Teimouri; Akram Sadat Hoseini; Neda Kinipour; Fatemeh Mahmoodi; Kobra Gholami Kiaee (Wolters Kluwer Medknow Publications, 2020)
INTRODUCTION: Children are among the most vulnerable groups in society, whose health is of prominent significance. Moreover, as a group of clients with special needs in the health care system, they require special attention. Therefore, the present study aimed to investigate the 0-14-year-old children's access to health centers in rural areas of Kermanshah Province, Iran. MATERIALS AND METHODS: In the present cross-sectional study, both the latest published demographic statistics related to the Population and Housing Census, announced by the Statistical Center of Iran in 2011, and the information about the public and private hospitals in the province, collected by Kermanshah University of Medical Sciences, were used as the basis for the analyses. In addition, given the importance of the spatial nature of the research, geographic information system was used for data analysis, and a buffer model was also applied. RESULTS: The results revealed that out of the total population of 0-14-year-old children residing in rural areas within 15,000 and 30,000-km radii of Kermanshah Province, 87.94% and 75.11% of girls versus 88.15% and 75.38% of boys lacked access to health centers, respectively. CONCLUSION: It was found out that the 0-14-year-old children's access to health centers was in poor condition in rural areas of Kermanshah Province, which would endanger the health of this age group.